The cure or the cause? Public opinions of elite sports` societal benefits and harms - De Rycke, J.; De Bosscher, V. (Sport in Society: Cultures, Commerce, Media, Politics, 2021)
Since the turn of the century, public investments in high performance sport are booming which requires policy makers to justify the expenses. Thus, governments predominantly argue that elite sport will trigger a range of benefits for the population. The latter is contested among academics as there is lack of robust evidence that supports the governmental claims. Moreover, evidence highlighting the `dark sides` of sport is mostly ignored. Surprisingly, valuable insights in how the tax-payer observes the societal impact of elite sport is scarce. Therefore, the research aim is to examine what negative and positive societal impact of elite sport is perceived by the population of Belgium (n = 1102). The results indicate that the Belgian population generally perceives less negative than positive societal impact of elite sport. The most negatively perceived impact relates to excessive costs, disturbed local living conditions and athletes` harmful physical and mental integrity issues.